2017
DOI: 10.1007/s13139-017-0476-7
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA PET/CT Imaging Predicting Intraprostatic Tumor Extent, Extracapsular Extension and Seminal Vesicle Invasion Prior to Radical Prostatectomy in Patients with Prostate Cancer

Abstract: Ga-PSMA I&T PET/CT prior to radical prostatectomy can contribute to presurgical local staging of prostate cancer. In this pilot study, Ga-PSMA I&T PET/CT showed promising results for prediction of lobe infiltration, ECE and SVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 35 publications
3
34
1
Order By: Relevance
“…Fendler et al (34) reported similar values of sensitivity and specificity for ECE and SVI detection. von Klot et al (35) reported a higher sensitivity of 90% and a similar specificity of 91% for the detection of ECE and similar values (75% and 100%) for the detection of SVI using 68 Ga PSMA-I&T PET/CT in a small cohort of 21 patients.…”
Section: Discussionmentioning
confidence: 74%
“…Fendler et al (34) reported similar values of sensitivity and specificity for ECE and SVI detection. von Klot et al (35) reported a higher sensitivity of 90% and a similar specificity of 91% for the detection of ECE and similar values (75% and 100%) for the detection of SVI using 68 Ga PSMA-I&T PET/CT in a small cohort of 21 patients.…”
Section: Discussionmentioning
confidence: 74%
“…Two additional articles were found upon additional screening of the reference lists. Finally, 12 studies including a total of 615 patients were included [26][27][28][29][30][31][32][33][34][35][36][37]. All 12 assessed SVI while 8 of them evaluated EPE.…”
Section: Literature Searchmentioning
confidence: 99%
“…All studies were of moderate to good quality, satisfying at 4 or more of the 7 domains in the QUADAS-2 tool except for one which only met 3 domains ( Figure 2). In the patient selection domain, 2 studies had unknown risk of bias as it was not clear whether the patient enrollment was consecutive or not [26,36]. One study had high concern for applicability as minority of the patients (2/50) had rising PSA after radiation treatment and these patients could not be separately analyzed from the other 48 with newly diagnosed prostate cancer [27].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…In the reference standard domain, all studies were at low risk of bias and concern for applicability. In the ow and timing domain, 6 studies had unknown risk of bias as the interval between PSMA-PET and prostatectomy was not provided [26,28,31,32,35,36].…”
Section: Quality Assessmentmentioning
confidence: 99%